Modelling real-time control options on virtual sewer systems. Issue 4 (1st July 2008) - Vanrolleghem, Peter A; Solvi, Anne-Marie; Muschalla, Dirk; De Keyser, Webbey; Dirckx, Geert; Weyand, Michael; Vandenberghe, Veronique; Benedetti, Lorenzo; Borsányi, Péter
Abstract : The study presents a benchmarking methodology to assess the performance of sewer systems and to evaluate the performance of real-time control (RTC) strategies by model simulation. The methodology is presented as a general stepwise approach. Two virtual sewer systems were modelled under four climate conditions. Catchment A represents a small system with medium RTC potential, while catchment B represents a large system with large potential according to PASST guidelines. The rain data represented Oceanic, Continental, Alpine and Mediterranean situations. Annual precipitation data was used. Tests included operation without RTC, and with two classic RTC strategies, aiming at, respectively, equal filling of storage tanks ("average filling"), and aiming at avoiding spilling just upstream of the treatment plant ("WWTP load"). The results have shown that similar RTC strategies perform differently under various climatic conditions and in sewer systems. The presented benchmarking methodology can be used to test the impacts of various climate scenarios on sewer systems that suffer from the limitations of static design.